Evidence for the rare decay [sigma]+→p[mu]+[mu]- - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; et al. (Physical review letters, 2018)
A search for the rare decay Σ+→pμ+μ− is performed using pp collision data recorded by the LHCb experiment at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. An excess of events is observed with respect to the background expectation, with a signal significance of 4.1 standard deviations. No significant structure is observed in the dimuon invariant mass distribution, in contrast with a previous result from the HyperCP experiment. The measured Σ+→pμ+μ− branching fraction is (2.2+1.8−1.3)×10−8, where statistical and systematic uncertainties are included, which is consistent with the standard model prediction.
Im Titel sind sigma und mu als griechische Buchstaben dargestellt
R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, S. Esen, C. Färber, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Schiller, P. Seyfert, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere] (LHCb Collaboration)
Gesehen am 07.05.2019